Acquisition of English personal and reflexive pronouns by L1 Malay speakers - Soo, Kum Yoke (2011)
This study investigates the acquisition of English personal and reflexive pronouns by L1 Malay speakers in relation to the issues of development and parameter resetting in SLA within the Universal Grammar (UG) framework. In particular, we test the Failed Functional Features hypothesis proposed by Hawkins and Chan (1997) that parametric values associated with functional categories which are not instantiated in the learners L1 at the critical period of learning are not available for acquisition in their L2. A hundred and fifty respondents participated in this study. They were divided into three groups of fifty respondents each based on their proficiency levels. The instruments used were an independent proficiency test, a Grammaticality Judgement Test, a Binding Test and an Elicited Translation Task. Malay personal pronouns do not differentiate gender and case features. Further, reflexive pronouns are not included in the Malay parts of speech. It is hence argued that these parametric differences between the learners’ L1 and L2 would impede acquisition as the learners are unable to reset L1 parameters beyond the critical period of learning. They would therefore have to find other mechanisms in order to fit their L1 settings within the constraints of UG. The findings show that with longer exposure to the L2, the intermediate and advanced groups were better able to acquire the pronouns compared to the elementary group. However, their performances were still far from native speaker competency. The results also suggest that features which were available in the learners L1 such as the number feature were better acquired compared to the gender and case features in personal pronouns. While reflexives were not available in the learners’ L1, they were still able to acquire them because a substitute form of reflexive-like pronouns was found in the learners’ L1. Comparatively, reflexive pronouns remained more difficult to attain. Binding property A tested showed that the learners found it difficult to acquire the property because of influence from the parametric values of the pronouns tested which were problematic.